Criteria of Coverage, Novelty, Search Printout and User Effort in Evaluating the Quality of Literature Searches - Nazlı Alkan (Türk Kütüphaneciliği)
In general terms, relevance is the basic criterion which designates the quality of literature searches. Users of searching sen’ices are principally interested in relevance, that is the number of relevant articles retrieved. Hcwever, relevance alone, in spite of its prime significance, does not satisfy the user needs in total. Users express some other needs in terms of quality. Such needs, which a searching service or system should meet, caused to originate some other quality criteria, namely the coverage, novelty, search printout and user effort. Besides relevance, these criteria are used to evaluate the performance and effectiveness of searching systems in terms of quality. The present study discusses the abovementioned criteria in detail. The functions of these criteria in designating the search effectiveness as well as their roles in search failures are stated. Some, approaches and solutions aiming at the practicing searchers in particular are offered to minimize search failures as well.